2011
DOI: 10.1111/j.1474-919x.2011.01200.x
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific and intraspecific differences in habitat use and their conservation implications for Palaearctic harriers on Sahelian wintering grounds

Abstract: The floodplains of the West‐African Sahel region have experienced extensive habitat transformation during the past four decades, coinciding with an impoverishment of raptor populations. We investigated foraging patterns of Palaearctic migratory Eurasian Marsh Harriers Circus aeruginosus, Pallid Harriers C. macrourus and Montagu’s Harriers C. pygargus on a floodplain system in northern Cameroon to assess species, sex‐ and age‐related habitat preferences. Sex and age have rarely been incorporated into general st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 71 publications
(118 reference statements)
1
25
1
Order By: Relevance
“…Although many studies have suggested possible conservation measures for the breeding grounds (e.g., Arroyo et al 2002, Donald et al 2007, Fuller et al 2007, Newton 2008, fewer have done so for the wintering grounds (e.g., Zwarts et al 2009, Walther et al 2010, 2011, Buij et al 2012, Limiñana et al 2012, Walther 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have suggested possible conservation measures for the breeding grounds (e.g., Arroyo et al 2002, Donald et al 2007, Fuller et al 2007, Newton 2008, fewer have done so for the wintering grounds (e.g., Zwarts et al 2009, Walther et al 2010, 2011, Buij et al 2012, Limiñana et al 2012, Walther 2016.…”
Section: Introductionmentioning
confidence: 99%
“…This may be related to differences in winter diets. The pallid harrier is a small-rodent specialist during breeding (Terraube et al, 2011) and small mammals and passerines contribute a large proportion of its total biomass consumption in winter (Buij et al, 2012). Hence, if pallid harriers reach an area of high vertebrate prey abundance in winter they may settle and remain there.…”
Section: Movements During and Between Wintersmentioning
confidence: 99%
“…Ideally, model predictions should be validated by field observations. Further research is also needed to identify the most profitable foraging habitats for pallid harriers at local scales, as done by Buij et al (2012). Detailed field studies on diet, prey (passerine birds, grasshoppers and small rodents) abundance and foraging success in different habitats (e.g.…”
Section: Perspectives and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations